Packaging Design of Roti Ganda Pematangsiantar Using Kansei Engineering Method and The Kano Model - Cut Ita Erliana; Aura Finkana; Syarifah Akmal (Performa: Media Ilmiah Teknik Industri, 2026)
Ganda Bakery is a legendary food business that has been operating since 1979, located at Jl. Kartini No. 21, Pematangsiantar, North Sumatra. The main issue lies in one of its flagship products, the jumbo bread filled with srikaya, which still uses basic packaging made of paper and rubber bands, without any brand identity or appealing design. This has led to consumer complaints, especially from tourists, as the packaging is considered unattractive, non-functional, and impractical for use as a long-distance food souvenir. This study aims to design new packaging that reflects consumer preferences using the Kansei Engineering approach and the Kano Model. An initial questionnaire was distributed to 96 respondents, with 77.1% stating that the current packaging is neither attractive nor functional. The analysis generated 190 Kansei words, which were refined into 15 core descriptors, including durable, eye-catching, innovative, strong identity, and informative. These were then analyzed through validity, reliability, and factor analysis. The Kano Model results indicated that attributes such as informative, high-quality materials, shape that matches the contents, clear text, visual appeal, durability, ease of use, and illustration belong to the One-Dimensional category. Meanwhile, attributes like innovative, strong identity, and colourful packaging fall under the Attractive category, while varied typography and unique design are categorized as Indifferent. The best design, scoring 4.31, features a gable box measuring 26 × 10 × 16 cm, which is ergonomic and practical, made from thick art carton with a protective layer, in bright yellow and dark brown, and includes complete, easy-to-read product information.